Dual-responsive controlled drug delivery based on ionically assembled nanoparticles - Cui, Wei (Langmuir : the ACS journal of surfaces and colloids, 2012)
Ionically assembled nanoparticles (INPs) have been formed from poly(ionic liquid-co-N-isopropylacrylamide) with deoxycholic acid through electrostatic interaction. The structure and properties of the INPs were investigated by using (1)H NMR, Fourier transform infrared (FTIR), transmission electron microscopy (TEM), dynamic light scattering (DLS), and so on. Due to pH-responsive deoxycholic acid (pK(a) = 6.2) and thermo responsive N-isopropylacrylamide included in the ionic complex, the INPs exhibit highly pH and thermal dual-responsive properties. The potential practical applications as drug delivery carriers were demonstrated using doxorubicin (DOX) as a model drug. With a lower pH (pH 5.2) and higher temperature (above 37 °C), structural collapse of the INPs occurred as well as release of DOX owing to protonated DA departure from the INPs and a lower LCST (lower critical solution temperature) at the pathological conditions. The result shows that 80% of DOX molecules were released from INPs within 48 h at pH 5.2, 43 °C, but only 30% of the drug was released within 48 h at 37 °C and pH 7.4. Moreover, drug-loaded INPs exhibit an inhibitory effect on cell growth